2021
DOI: 10.1177/10547738211003273
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a Clinical Risk Triage Score for Adult Emergency Department

Abstract: Emergency triage is crucial for the treatment and prognosis of emergency patients, but its validity needs further improvement. The purpose of this study was to identify a risk score for adult triage. We conducted a regression analysis of physiological and biochemical data from 1,522 adult patients. A 60-point triage scoring model included temperature, pulse, systolic blood pressure, oxygen saturation, consciousness, dyspnea, admission mode, syncope history, chest pain or chest tightness, complexion, hematochez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…At present, in the research on the related factors of early identi cation of critical emergency patients, the factors involved in identi cation include: temperature, HR, R, SBP, SpO2, pain score, consciousness, pupil, mental state, blood sugar, blood routine, creatinine, blood potassium, etc., but there is no consensus yet [3,8,[13][14] . In this study, through multivariate logistic regression analysis, it is found that the risk factors for early judgment of critical risk of emergency patients are gender, age,HR, R, SBP, SpO2, consciousness, pupil, mental state and pain score, while temperature, tip, urine volume and hyperhidrosis are not independent risk factors.…”
Section: Risk Factors Of Prediction Modelmentioning
confidence: 99%
“…At present, in the research on the related factors of early identi cation of critical emergency patients, the factors involved in identi cation include: temperature, HR, R, SBP, SpO2, pain score, consciousness, pupil, mental state, blood sugar, blood routine, creatinine, blood potassium, etc., but there is no consensus yet [3,8,[13][14] . In this study, through multivariate logistic regression analysis, it is found that the risk factors for early judgment of critical risk of emergency patients are gender, age,HR, R, SBP, SpO2, consciousness, pupil, mental state and pain score, while temperature, tip, urine volume and hyperhidrosis are not independent risk factors.…”
Section: Risk Factors Of Prediction Modelmentioning
confidence: 99%